Determinant of Net Interest Margin Banking In Indonesia, During The Period 2009 - 20018 - Siti Mariam; Fika Aryani; Dhinda Siti Mustikasari; Abdul Haeba Ramli (Yayasan Ilomata, 2021)
The purpose of this study is to examine the effect of Loan Growth, Unemployment, BOPO, CAR, Inflation, and Exchange Rate in relationship with Net Interest Margin. The research object used is banking data BUKU I to BUKU IV 2009-2018 published by Financial Service Authority, known as OJK. The analysis technique used is panel data regression analysis with Eviews 9.0 analysis tool. The results showed that the variables which consist of Loan Growth, and Unemployment had a significant positive effect on Net Interest Margin. Other independent variables, which consist of BOPO and Exchange Rate had a significant negative effect on Net Interest Margin. While CAR and Inflation do not show a significant impact on Net Interest Margin.